Tìm họ nguyên hàm của hàm số \(f(x)=\dfrac{2x^2+x-1}{x^2}\).
![]() | \(\displaystyle\int\dfrac{2x^2+x-1}{x^2}\mathrm{\,d}x=2+\dfrac{1}{x}-\dfrac{1}{x^2}+\mathrm{C}\) |
![]() | \(\displaystyle\int\dfrac{2x^2+x-1}{x^2}\mathrm{\,d}x=2x+\dfrac{1}{x}+\ln|x|+\mathrm{C}\) |
![]() | \(\displaystyle\int\dfrac{2x^2+x-1}{x^2}\mathrm{\,d}x=x^2+\ln|x|+\dfrac{1}{x}+\mathrm{C}\) |
![]() | \(\displaystyle\int\dfrac{2x^2+x-1}{x^2}\mathrm{\,d}x=x^2-\dfrac{1}{x}+\ln|x|+\mathrm{C}\) |
Chọn phương án B.
Ta có: \(f(x)=\dfrac{2x^2+x-1}{x^2}=2+\dfrac{1}{x}-\dfrac{1}{x^2}\).
\(\begin{aligned}\Rightarrow\displaystyle\int f(x)\mathrm{\,d}x&=\int\left(2+\dfrac{1}{x}-\dfrac{1}{x^2}\right)\mathrm{\,d}x\\
&=2x+\ln|x|+\dfrac{1}{x}+C.\end{aligned}\)